Azotobacter paspali sp. n. A nitrogen fixing bacteria in the rhizosphere of Paspalum - Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2024)
A new nitrogen fixing bacteria was found to occur in large numbers on the root surface (rhizoplan) and less abundant in the rizosphere of Paspalum notatum and Paspalum plicatum. Seventy five out of 76 soil samples from the root surface of P. notatum, and two out of three soil samples from P. plicatum contained the new organism. Two root surface soil samples each from P. convexum, P. vaginatum, P. fasciculatum, P. maritimum, and P. erianthum did not contain the new bacteria. Also soil samples from the root surface of 81 other pasture plants, including more than 32 species of the family Gramineae, 8 species of the family Leguminosae, and other plants not identified, were all negative. The new bacteria was found in soils with a wide pH range (4.9 to 7.8) although in culture medium good growth was obtained only above the pH 5.5. There is normally a higher pH on the root surface of Paspalum notatum than in a surrounding acid soil. The new organism can be easily identified on silica-gel plates with calcium citrate, inoculated with appropriated soil by a yellow soluble pigment and numerous small colonies which solubilize the calcium citrate. On N-free agar medium with brom-thymol-blue, colonies are caracteristically flat with a deep orange center. In liquid N-free medium, rapid growth occurs which precipitates in flockes and settles to the bottom. A yellow soluble pigment is formed (not by all strains, however) when incubate without shaking. A violet to brown pigment is formed in liquid medium with calcium citrate when incubated on a rotary shaker. In liquid medium with sucrose, growth stopped when pH 5.2 was reached by the acid production of the proper organism. When the medium was neutralized or when calcium citrate was used as carbon source, growth continued until all of the substrate was used. In suitable culture medium (N-free medium with glucose, sucrose, maltose or calcium citrate), after 24 hours the organisms appear as uniform, very motile rods of 1.2 x 4 - 10µ. The cells grow rapidly and after 48 hours filaments of varying sizes become visible which may reach a length of 60 µ or more. After three days the culture represents a mixture of roods and filaments of all sizes and of cysts which are much like those of the known Azotobacter species. The organism is Gram negative and stains with Gentian Violet (0.05%) show homogeneous plasma in young cells and granulated plasma in older cultures. The filaments often show chains of terminal granules. There was no growth of the organism in litmus milk or nutrient broth even in the presence of glucose. Good growth was observed in N-free medium with glucose, sucrose, galactose, maltose, methanol, ethanol, buthanol, mannitol, glicerol, lactate, acetate, citrate, starch and dextrin. Little or no growth was observed with arabinose, lactose, mannose, laevulose, tartarate, benzoate, oxalate and amylic alcohol. Acid production was observed with all substances that gave good growth except the salts of the acids. The organism showed best growth at quite high temperatures, 37.°C being better for the development on silica gel plates than 34.°C. The nitrogen fixing capacity in culture medium was comparable with that of other Azotobacter spp., 30.4 mg N/1 g sucrose being the highest value observed. Following the given characteristics the bacteria was placed in the genus Azotobacter. It differed from all known specied of this genus by the following features: 1 - Characteristic growth on silica gel plates with calcium citrate as carbon source and incubated at 34 to 37.°C. After 4 to 5 days yellowing of the silica-gel followed by the appearance of numerous small colonies which solubilize the citrate and give the impression of many little holes. 2 - Filamentous form of young cells during the logaritmic growth phase which can not be confounded with involution forms. 3 - Inability to use arabinose, lactose, mannose, laevulose and tartarate. Due to the fact that the new organism was found exclusively on the roots of two species of Paspalum the name Azotobacter paspali sp.n. is proposed. The possibility of this Azotobacter representing the intermediate step in the evolution of the legume symbiosis from nonsymbiotic nitrogen fixers, is discussed. During the studies for this paper, in 15 soil samples, another organism was observed to occur on the root surface of several plants. Its was identified as Derxia sp. probably the species recently described by Jensen, as occuring in Indian soils.